Analisis CAR, BOPO, ROA, NPF Terhadap Dana Pihak Ketiga Pada Bank Syariah Indonesia Periode Covid19 - Nuriana, Mutia Azizah; Sanusi, Makhda Intan; prastiwi, iin emy (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
Based On The No.10/14 / DPbS this is an explanation and technical guidance from PBI No. 9/19/PBI/2008 dated December 17, 2007 on the implementation of Sharia principles in fund raising and fund distribution activities as well as Islamic Bank services, where this PBI is a refinement / amendment of PBI No. 7/46 / PBI 2006 dated November 14, 2005 on the contract for the collection and distribution of funds for banks that carry out business activities based on Sharia principles. The financial health condition of banking is closely related to third party funds, so the condition of CAR, BOPO, ROA and LDR in Islamic financial institutions has an effect on third party funds. So in this qualitative research method provides answers to how the influence of CAR, BOPO, ROA and LDR on third-party funds. Financial Data that researchers have pulled from ojk financial data throughout Sharia commercial bank institutions from 2019 to 2024 make secondary research techniques. This study used test data analysis techniques using multiple linear regression danuji hypothesis (t test) then the data were analyzed using SPSS version 20. The test results obtained as follows, Based on the results of the analysis in this study, it can be concluded that there is a positive and significant influence between the independent variables (CAR, BOPO,ROA, and NPF) partially to the dependent variable (third party funds).